2012
DOI: 10.1093/chromsci/bms119
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Monitoring of Selective Serotonin Reuptake Inhibitors in Human Urine, Plasma and Oral Fluid by Reverse-Phase High Performance Liquid Chromatography

Abstract: A simple and rapid reverse-phase high-performance liquid chromatography method is developed for the simultaneous determination of selective serotonin reuptake inhibitors (sertraline, citalopram, paroxetine and fluoxetine) in urine, plasma and oral fluid. Separation was performed on a Crestpack-18 column (4.6 × 250 mm × 5 µ) within 17.5 min. The mobile phase was composed of water (50 mL) [with glacial acetic acid (0.15 mL) + triethyl amine (0.30 mL)]-acetonitrile (40 mL)-methanol (10 mL), delivered isocraticall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 39 publications
1
4
0
Order By: Relevance
“…When LLE with dichloromethane was applied, the recovery of CIT was similar to findings in the literature, where ether was used for extraction [19]. It can, therefore, be confirmed that absolute recovery obtained in this study is consistent with literature data.…”
Section: Resultssupporting
confidence: 90%
See 4 more Smart Citations
“…When LLE with dichloromethane was applied, the recovery of CIT was similar to findings in the literature, where ether was used for extraction [19]. It can, therefore, be confirmed that absolute recovery obtained in this study is consistent with literature data.…”
Section: Resultssupporting
confidence: 90%
“…These relatively low values may be due to the simultaneous determination of nine antidepressants and some of their metabolites in saliva. The recovery of CIT and DCIT from plasma following LLE procedure stood at approximately 77 and 53%, respectively [8], while the efficiency of extraction from saliva for citalopram was 94% [19].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations